Forced Molting: A Technique to Improve The Egg Production of Duck in The Next Laying Cycle - Argono Rio Setioko (Indonesian Center for Animal Research and Development, 2005)
Molting is a physiological process that involves the shedding of old feathers and the growth of the new one in birds. It is affected by hormonal, where the ovary regresses and the egg production automatically ceases. Although molting is a natural phenomena, this can be induced artificially that commonly called